Oriental Manuscripts in Shri Partap Singh (SPS) Library Srinagar, Kashmir(India). - Khan, Kamran (2014)
The paper attempts to survey the manuscript treasures of Sri Pratap Singh (SPS) library deciphering the cultural and heritage wealth of Jammu & Kashmir state in oriental languages. It provides a general introduction and present condition of these rare collections. The paper is useful for researchers related to oriental disciplines, students of Library and Information Science, library professionals and all those who have interest in rare and valuable manuscripts available in Kashmir.